The possibilities of personnel development principle adaptability in personnel training - Asta Stankevičienė; Aušra Liučvaitienė; Diana Volungevičienė (Business: Theory and Practice, 2008)
The article analyzes the conception of personnel training in accordance with the publications of Lithuanian and foreign authors. Therewith the survey was carried out to investigate the possibilities of applying the principle of personnel training in Lithuanian enterprises. This survey was carried out using the expert questioning of top managers and it provides the possibility of assessing the situation and problems of personnel training. Finally, the ways how to apply personnel training in Lithuanian enterprises are discussed in the article.